The evolution of geomagnetotail magnetic flux in isolated substorms. (November 2017) - Yang, Y.Y.; Shen, C.; Rong, Z.J.; Dunlop, M.; Shen, X.H.; Huang, J.P.; Chen, Z.Q.
Abstract: The magnetic field energy stored in geomagnetotail released during a substorm period, cause significant magnetic disturbance of the space environment. The quantitative relationship between the magnetic field energy and the level of substorm activity, however, is still unclear, although many studies have qualitatively revealed the correlation between them. Here, using data from four selected isolated substorm cases, the evolution of the magnetic flux (MF) in the magnetotail observed by Cluster is quantitatively surveyed. The results from the four cases demonstrate that the evolution of magnetotail MF is closely related to the phases of substorm development. For quiet time, the magnetotail is in the ground state with MF being about 0.6 GWb. During the growth phase, however, as the substorm develop the MF keeps increasing, the substorm onset is triggered when the MF has increased up to some threshold. The comparison between the four cases shows that the accumulation of more magnetic field energy corresponds to more released energy, and consistently, the more intense a substorm can be powered. The study also finds that there is an imbalance between the increased and decreased MF amplitude, indicating that the substorm may not be the only way to release the stored magnetotail energy. Highlights: The geomagnetotail magnetic flux are calculated with Cluster observation. The evolution of substorms with different strength are quantitatively analyzed. The stored and released energy is imbalance during the whole substorm process.